SWAT model-based quantification of the impact of land use land cover change on sediment yield in the Fincha watershed, Ethiopia - Regasa, Motuma Shiferaw; Nones, Michael (Frontiers in Environmental Science, 2023)
In recent years, Ethiopia is facing problems due to soil erosion, mainly because of the conversion of natural vegetation into cultivated land to answer to increasing human pressure. Such changes in coverage are fostering soil erosion, which is also affecting dam reservoirs, because of the increasing sediment yield entering the lake. The present study focuses on the Ethiopian Fincha watershed and takes advantage of the potentiality of the Soil and Water Assessment Tool (SWAT) model, to investigate how land use land cover changes impact soil erosion and the consequent sediment yield entering the Fincha Dam. The SWAT model was calibrated and validated using time series data of stream flow and sediment covering the period 1986-2008, and its performance was evaluated by looking at the coefficient of determination, Nash-Sutcliffe simulation efficiency, and per cent bias. Once validated, the SWAT model was applied to derive sediment yield for the future thirty years, based on forecasted land use land cover conditions. The results show that the mean annual soil loss rate increased from 32.51 t ha-1 in 1989 to 34.05 t ha-1 in 2004, reaching 41.20 t ha-1 in 2019. For the future, a higher erosion risk should be expected, with the annual soil loss rate forecasted to be 46.20 t ha-1 in 2030, 51.19 t ha-1 in 2040, and 53.98 t ha-1 in 2050. This soil erosion means that sediments transported to the Fincha Dam, located at the watershed outlet, increased significantly in the last thirty years (from 1.44 in 1989 to 2.75 mil t in 2019) and will have the same trend in the future (3.08 to 4.42 mil t in 2020 and 2050, respectively), therefore highly affecting the Fincha reservoir services in terms of reduction of water volume for irrigation and hydroelectric power generation. By providing possible medium/long-term scenarios, the present work can help land planners and decision-makers in developing future land management strategies based on actual projections, eventually aiming to reduce soil erosion at the watershed scale and guarantee the sustainable development of the Fincha region and its key hydraulic infrastructures.